Global philosophy of religion(s) - Harrison, Victoria ca. 20./21. Jh. (Religious studies, 2020)
Drawing on the work of Mark Siderits, Jay Garfield, and others, I introduce a global approach to the philosophy of religion that is inspired by ‘fusion’, ‘engagement’, or ‘confluence’ philosophy. To globalize the philosophy of religion requires more than expanding its traditional disciplinary scope or broadening its range of questions; it requires philosophers who are conversant in more than one philosophical tradition. I argue that this approach offers a viable way to develop the discipline by providing a platform for deep and authentic engagement in philosophical inquiry that crosses traditional religious and philosophical boundaries.